Penelitian tentang Blog - Kartini Kartini; Anggriani Anggriani; Mehlan Ainul Fidaus; Sopa Rosa Lubis (Universitas Muhammadiyah Enrekang, 2022)
Blog means a kind of online diary. Blog owners generally write a lot of notes into his blog, like a diary. The results from the writing of the pen can be viewed online via the internet. In addition, blog visitors can also comment on the blog owner's writing. In addition to writing, you can also add images, videos, and even upload files. so that visitors can download the file that we pour. the following is a blog of the many blogs on the internet: 1. Political blogs, two. Live blog, 3. Topic blog, 4. Health blog, 5. Language blog, 6. Tourism blog, 7. Research blog, 8. Rules blog, 9. Media blog, 10. Trust blog, 11. Education blog, 12. Steering Blog, 13. Business blog, 14. Troubles Block. The first requirement to produce a blog means to have an email. Email is electronic mail that is commonly used to send letters on the internet. In addition to the function of sending letters, Email can also be used to register a blog. There are so many free email providers that are scattered today, including Gmail.com, yahoo.com, hotmail.com, and so on. Learning media, the word media comes from Latin, which means the general form of the origin of the medium, the limitations on the definition of media are very broad, but we limit it to educational media, namely media used as senses and materials for learning activities. The benefits of blogs for lecturers are that blogs can function as a writing learning medium. with blogs, lecturers learn and train their abilities in forming a scientific work or written paper. Before appearing in the field of writing at every official event such as; writing competitions, or certifications, it would be better if the lecturers used blogs as a writing learning medium first.